1986
DOI: 10.2214/ajr.146.6.1173
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic focal bacterial nephritis: findings on gray-scale sonography and CT

Abstract: Schoolof Medicine, 333 Cedar St., New Haven, CT 06510. Address reprint requests to C. M. Rigsby.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 4 publications
(2 reference statements)
1
19
0
Order By: Relevance
“…The characteristic CT finding in these cases is a patchy area of delayed contrast enhance- Dec. 9 D ec.12 ment in the renal parenchyma [1,4,7], The pathophysio logical mechanism of the patchy enhancement has not been explained clearly, although this phenomenon has been considered to be compatible with renal vasoconstric tion. However, delayed patchy cortical excretion of con trast media by the kidney, which is not a phenomenon specific to EIARF, has been reported in hypovolemia [8], the recovery phase from rhabdomyolysis-related ARF [9], focal bacterial nephritis [10,11], and hemorrhage fever with renal syndrome [12], Furthermore, in our case the diminishment of blood flow and the increment of arterial resistance was observed in all four of the segmental arter ies examined by Doppler. Due to limited resolution, we cannot conclude that all of the intrarenal arteries were constricted.…”
Section: Case Reportsupporting
confidence: 46%
“…The characteristic CT finding in these cases is a patchy area of delayed contrast enhance- Dec. 9 D ec.12 ment in the renal parenchyma [1,4,7], The pathophysio logical mechanism of the patchy enhancement has not been explained clearly, although this phenomenon has been considered to be compatible with renal vasoconstric tion. However, delayed patchy cortical excretion of con trast media by the kidney, which is not a phenomenon specific to EIARF, has been reported in hypovolemia [8], the recovery phase from rhabdomyolysis-related ARF [9], focal bacterial nephritis [10,11], and hemorrhage fever with renal syndrome [12], Furthermore, in our case the diminishment of blood flow and the increment of arterial resistance was observed in all four of the segmental arter ies examined by Doppler. Due to limited resolution, we cannot conclude that all of the intrarenal arteries were constricted.…”
Section: Case Reportsupporting
confidence: 46%
“…The diffuse form of acute pyelonephritis may cause global enlargement, poor enhancement of renal parenchyma, absent excretion of contrast and streakiness of fat. Hemorrhagic bacterial nephritis which is relatively uncommon shows hyperattenuating areas representing parenchymal bleeding on non-contrast scan [5] . …”
Section: Acute Pyelonephritismentioning
confidence: 99%
“…On ultrasonography, most APN appears normal; however, various findings can be revealed, such as single or multiple hyperechoic areas, kidney enlargement, pelvic wall thickening, hypoechoic areas, and perirenal fat involvement [3]. AFBN is characterized by renal masses without liquefaction on sonography or CT, and it can have either hyperechoic or hypoechoic echogenicity [1,[5][6][7][8]. Rathaus et al reported that 47 of 52 cases of AFBN showed a hyperechoic mass, whereas 5 cases showed hypoechoic [1].…”
Section: Discussionmentioning
confidence: 99%
“…That is, a hyperechoic lesion may indicate the incipient stage of AFBN and its echogenicity may change to hypoechoic with progression. Rigsby et al suggested that increased echogenicity reflects an acute hemorrhage resulting from the venous abnormalities and obstruction [2,8], which was evidenced by one of the histopathological findings of AFBN [2]. Although there are no reports on serial histopathological findings of AFBN, low echogenicity followed by high echogenicity may reflect liquefied lesions progressing to renal abscess.…”
Section: Discussionmentioning
confidence: 99%